1999
DOI: 10.1259/bjr.72.856.10474496
|View full text |Cite
|
Sign up to set email alerts
|

Cross-calibration, precision and patient dose measurements in preparation for clinical trials using dual energy X-ray absorptiometry of the lumbar spine.

Abstract: Large, multicentre clinical trials using DXA to monitor bone density following intervention are now common. At the same time, several different bone densitometers and calibration phantoms are currently in use. The aim of this study was to document the technical information required on cross-calibration of equipment, reproducibility and patient dose before commencing a multicentre clinical trial. To this end, we obtained an in vitro and in vivo cross-calibration of two machines (a Hologic QDR 2000 and a Lunar D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…For bone mineral calibration Norland and Hologic use hydroxyapatite alone, whereas Lunar takes into account that bone contains also fat (TOTHILL 1995). Lunar devices appear to measure systematically higher values for BMC and BMD than Norland and Hologic devices (LASKEY et al 1991, MAZESS et al 1991, TOTHILL et al 1994a, CAWTE et al 1999. This was also demonstrated in the present study where Lunar yielded significantly larger BMD and BMC values.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…For bone mineral calibration Norland and Hologic use hydroxyapatite alone, whereas Lunar takes into account that bone contains also fat (TOTHILL 1995). Lunar devices appear to measure systematically higher values for BMC and BMD than Norland and Hologic devices (LASKEY et al 1991, MAZESS et al 1991, TOTHILL et al 1994a, CAWTE et al 1999. This was also demonstrated in the present study where Lunar yielded significantly larger BMD and BMC values.…”
Section: Discussionsupporting
confidence: 77%
“…Differences in the measurement of bone area are caused by the capability of a device to accurately detect the bone edge, including differences in the threshold value for bone detection. CAWTE et al (1999), comparing Lunar and Hologic devices, reported higher BMD values from Lunar and assumed that the edge detection algorithm of the Lunar device eliminated more low density bone than the Hologic device resulting in a smaller area and a consequently higher BMD. Comparing a fan beam with a pencil beam DXA device (Lunar), CRABTREE et al (2005) found a smaller bone area to be associated with a lower BMC in the fan beam device, but the resulting BMD was not different.…”
Section: Discussionmentioning
confidence: 99%
“…There is about a 15% difference in BMD between Hologic and GE Lunar instruments [9] and the variation between DXA instruments from one manufacturer is of the order of a few percent in vivo and 1% in vitro [1][2][3]. This variation limits the applicability of standardized BMD [8].…”
Section: Discussionmentioning
confidence: 99%
“…The alternative is to use a cross-calibration phantom, and several have been produced over the years. All have some limitations [7,9]. The aim of this project was to compare the more recently available Bona Fide Phantom and two other phantoms used for cross-calibration (the European Spine Phantom and the GE Lunar Aluminum Spine Phantom) with an in vivo cross-calibration.…”
Section: Introductionmentioning
confidence: 99%
“…The current clinical standard, which is site-specific bone mineral density (BMD) assessment using dual energy x-ray aborptiometry (DXA) (1,4), is only moderately effective in predicting the occurrence of vertebral fractures (11). Numerous researchers have speculated that DXA is an inaccurate measure of vertebral fracture risk potential because it is structurally simplistic, i.e., it reflects only volume averaged material properties, and they have focused their efforts on developing more sophisticated mechanical models of vertebral body fractures (2,8,9,14,15,19,23,36).…”
Section: Introductionmentioning
confidence: 99%